Critical Discourse Analysis Controversial Statement Of God Is Not An Arabic In The Perspective Of Mantiq Science - Elin Parina; Ratu Mutialela Caropeboka (LEGAL BRIEF, 2022)
This research aims to analyze a video content of controversy the statement "God is not an Arab" which had become a controversy among the public. The analysis was carried out based on the perspective of mantic science using the critical discourse analysis approach proposed by Norman Fairclough. This study uses a descriptive qualitative method. This research data was obtained from the contents of the da'wah message delivered by ustad Adi Hidayat in a video on a YouTube channel. Invalidating the results of the analysis, the researcher interviewed a figure in the field of Islamic philosophy, wto further analyzethe statement. The results of this study are first, regarding God, not Arabs, tex,tually, ustad Adi stated that there was an error in the syllogism, because between God acres are two different things, and if they are the same, it will open up opportunities for a human to claim himself as God. Therefore, logically, the statement contains errors. Second, regarding praying using Arabic, ustad Adi said that in praying it is permissible to use one's language for generators, but in worship practice, it must be by the Messenger of Allah, one of which is by using Arabic.